EKSISTENSI TOKOH UTAMA DAN PENGARUHNYA TERHADAP KEHIDUPAN SOSIAL MASYARAKAT DALAM MANGA DOSHIRO DE GOZARU KARYA NISHIMORI HIROYUKI - Yasa, I Ketut Warsita (Humanis; Volume 13. No.2. Nopember 2015)
The study analyzed existence of the main character and its influence in social life in comics Doshiro De Gozaru by Nishimori Hiroyuki. The Purpose of this study is to determine the exsistence of the character Doshiro and its influence on social life. The Analysis of exsistence of the main character of Doshiro is using the theory of existentialism of Sartre (2007). The results of this study indicate that exsitence of the main character of Doshiro arises because of the conflict and anxiety that occurs. In addition, the existence of which was found there that are authentic is acting on his own strength and willing to listen to the sound of his own conscience alone. And there are no authentic conscience. In comic Doshiro de gozaru existence Doshiro figures also affect the social life like, affect the consciousness of the thugs, the formation of groups who repent, and the influence of his own family.
Keywords: Existence, Conflict, Influence.